Pengaruh Tenaga Kerja (Human Capital) Dan Daya Dorong Investasi Terhadap Pertumbuhan Ekonomi Provinsi Papua (Studi Kasus) - Abdul Rasyid (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
The economic development efforts of the Papua province should focus on increasing employment opportunities and increasing investment as a stimulus to economic growth, thereby distributing community opportunities in every productivity Can be acquired for community welfare and economic development. Therefore, each autonomous region has the freedom to develop all potential and assets owned, especially the potential of natural resources that can be used as a mainstay asset in the development of regional economies in general. Therefore, it is necessary to analyze how the influence of Labour (Human Capital) and the power of investment in economic growth in Papua province (case study).The results showed that: the provision of employment opportunities in the Papua province is influenced by investment and real investment affects the provision of employment opportunities. This is because there is a lot of investment supported by the Government through a development financing budget that use more oriented to the development of sectors that are less absorbing workforce. Investment and Labour, both have no positive effect on the percapita income and economic growth.